Deoxycholic Acid as a Modifier of the Permeation of Gliclazide through the Blood Brain Barrier of a Rat - Mladena Lalić-Popović; Velibor Vasović; Boris Milijašević; Svetlana Goločorbin-Kon; Hani Al-Salami; Momir Mikov (Journal of Diabetes Research)
Major problem for diabetic patients represents damage of blood vessels and the oxidative stress of the brain cells due to increased concentration of free radicals and poor nutrition of brain cells. Gliclazide has antioxidative properties and poor blood brain barrier (BBB) penetration. Bile acids are known for their hypoglycemic effect and as promoters of drug penetration across biological membranes. Accordingly, the aim of this study is to investigate whether the bile acid (deoxycholic acid) can change the permeation of gliclazide, through the blood brain barrier of a rat model type-1 diabetes. Twenty-four male Wistar rats were randomly allocated to four groups, of which, two were given alloxan intraperitoneally (100 mg/kg) to induce diabetes. One diabetic group and one healthy group were given a bolus gliclazide intra-arterially (20 mg/kg), while the other two groups apart from gliclazide got deoxycholic acid (4 mg/kg) subcutaneously. Blood samples were collected 30, 60, 150, and 240 seconds after dose, brain tissues were immediately excised and blood glucose and gliclazide concentrations were measured. Penetration of gliclazide in groups without deoxycholic acid pretreatment was increased in diabetic animals compared to healthy animals. Also in both, the healthy and diabetic animals, deoxycholic acid increased the permeation of gliclazide through that in BBB.